Classification of functioning and impairment: The development of ICF core sets for autism spectrum disorder - Bölte, Sven; De Schipper, E.; Robison, J.; Wong, V.; Selb, M.; Singhal, N.; de Vries, P.; Zwaigenbaum, L. (2014)
Given the variability seen in Autism Spectrum Disorder (ASD), accurate quantification of functioning is vital to studying outcome and quality of life in affected individuals. The International Classification of Functioning, Disability and Health (ICF) provides a comprehensive, universally accepted framework for the description of health-related functioning. ICF Core Sets are shortlists of ICF categories that are selected to capture those aspects of functioning that are most relevant when describing a person with a specific condition. In this paper, the authors preview the process for developing ICF Core Sets for ASD, a collaboration with the World Health Organization and the ICF Research Branch. The ICF Children and Youth version (ICF-CY) was derived from the ICF and designed to capture the specific situation of the developing child. As ASD affects individuals throughout the life span, and the ICF-CY includes all ICF categories, the ICF-CY will be used in this project ("ICF(-CY)" from now on). The ICF(-CY) categories to be included in the ICF Core Sets for ASD will be determined at an ICF Core Set Consensus Conference, where evidence from four preparatory studies (a systematic review, an expert survey, a patient and caregiver qualitative study, and a clinical cross-sectional study) will be integrated. Comprehensive and Brief ICF Core Sets for ASD will be developed with the goal of providing useful standards for research and clinical practice and generating a common language for functioning and impairment in ASD in different areas of life and across the life span. Autism Res 2014, 7: 167-172.